Optimasi Rute Kendaraan pada Pendistribusian Produk Agroindustri Menggunakan Metode Sweep dan Nearest-Neighbor - Solihin, Solihin; Muhendra, Rifki; Widyantoro, Murwan; Munawir, Al (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2023)
AI Company is a producer of agro-industrial products. Products produced from the agricultural industry, for example vegetables, fruit and so on. These products are easily damaged. Therefore, the transportation system for product distribution needs to be carried out in the shortest possible time. Besides that, vehicle use produces air pollution and greenhouse gases which trigger global warming. This research proposes the Sweep and Nearest-Neighbor methods to minimize vehicle route distances in distributing products from AI companies to various customers. By minimizing the distance traveled, it is hoped that it can also contribute to reducing CO2 emissions. The Sweep method is intended to cluster destination locations and the Nearest-Neighbor algorithm is used to get the shortest route so that the shortest distance is obtained. From the results of this study, before optimization, the usual delivery distance for goods carried out by AI companies was 10,077.00 km and decreased to 9,286.00 km per year after optimization. The CO2 emissions per year before optimization were 2147.95 kgCO2e, while after optimizing the distance traveled, CO2 emissions decreased to 1979.13 kgCO2e.